PEMETAAN KONTRAKSI CIRIC-MATKOWSKI PADA RUANG METRIK TERURUT - Mariatul Kiftiah (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2014)
In this paper, a new concept about Ciric-Matkowski contraction mapping in ordered metric space (related to ≤) is contructed. Different from the metric space, the Ciric-Matkowski contraction mapping in ordered metric space does not imply that the mapping to be continous. Next, some fixed point theorem of the Ciric-Matkowski contraction mapping in ordered metric space which is continous and not are proved. The result shows that the theorems do not guarantee the existence and uniqueness fixed point in ordered metric space. Adding comparable condition in it space then its mapping have a unique fixed point.